1999
DOI: 10.1116/1.590634
|View full text |Cite
|
Sign up to set email alerts
|

Advances in field emission displays phosphors

Abstract: Recent advances in the phosphors used for field emission displays (FEDs) are discussed. After reviewing the range of voltages and phosphors being used in first generation devices, the improved properties of future generation phosphors are reviewed. Specifically, next generation displays will require better low voltage efficiencies, chromaticity, saturation behavior, and maintenance. Possible routes to achieve these improvements are discussed. The improved understanding of the role of charging and surface recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 45 publications
3
121
0
Order By: Relevance
“…It has been shown that understanding the role of a surface in photo-and cathodoluminescence phenomena requires studying the nature of the surface states, local electric fields due to trapped charges and the band structure at surfaces [70][71][72]. For example, luminescence intensity in Y 2 O 3 :Eu and Y 2 SiO 5 :Tb (under low-voltage CR excitation) can to an extent be controlled by impressed external electric fields over phosphor layer [73].…”
Section: Final Research Task Reportsmentioning
confidence: 99%
“…It has been shown that understanding the role of a surface in photo-and cathodoluminescence phenomena requires studying the nature of the surface states, local electric fields due to trapped charges and the band structure at surfaces [70][71][72]. For example, luminescence intensity in Y 2 O 3 :Eu and Y 2 SiO 5 :Tb (under low-voltage CR excitation) can to an extent be controlled by impressed external electric fields over phosphor layer [73].…”
Section: Final Research Task Reportsmentioning
confidence: 99%
“…Thus, the penetration depth of the primary electrons is small and the phosphors exhibit more severe surface degradation. During operation, the phosphor decomposition products generated by electron stimulated processes can poison the emitter cathodes [2]. This lowers the efficiency of the phosphor and shortens the life of the device.…”
mentioning
confidence: 99%
“…However, vacuum fluorescent displays (VFD) utilizing these mixes have a short life time compared to those using traditional high conductivity ZnO:Zn. One serious impediment which limits the use of conventional sulfide phosphors is the electron stimulated decomposition which generates harmful gases such as S, SO and SO 2 [2]. The sulfur related gases coming from the phosphor can dramatically reduce the electron emission efficiency of the cathodes and the degradation of the phosphor surface also leads to deteriorated phosphor performance.…”
mentioning
confidence: 99%
“…Low-voltage operation can also reduce electron beam stimulated chemical reactions which have been associated with phosphor and cathode degradation in FEDs. 2 Because of the small penetration depth at low voltages, the loss processes are believed to be associated with surface recombination, and thus, the surface coating and encapsulation of phosphors is an important technique to improve low-voltage cathodoluminescence (CL) and chemical stability and to reduce outgassing. Coatings can also reduce phosphor surface degradation (such as oxidation) associated with display fabrication processes thus reducing the surface dead-layer thickness and passivating surface recombination centers.…”
mentioning
confidence: 99%